2021
DOI: 10.5539/jfr.v10n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Economics in the COVID-19 Pandemic

Abstract: The consequences of the COVID-19 pandemic crisis for both food safety and especially the economic sustainability of food production in Canada and around the globe are explored. A full analysis is made of the nature of the virus, and it is spread as they relate to the forces of globalization which have created a global food supply chain, with a focus on the weaknesses of a global supply chain that fell prey to the COVID-19 virus and its associated economic effects. Comparison was made to past outbreaks of Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These are important findings, suggesting that the stigma related to SARS-CoV-2 might further deepen standing racial inequalities related to nutrition and health [90]. However, it was largely inferred that the pandemic has generally pushed consumers to worry more about food safety than before [91,92].…”
Section: Risk Perception Affecting Behavior Science Claritymentioning
confidence: 99%
“…These are important findings, suggesting that the stigma related to SARS-CoV-2 might further deepen standing racial inequalities related to nutrition and health [90]. However, it was largely inferred that the pandemic has generally pushed consumers to worry more about food safety than before [91,92].…”
Section: Risk Perception Affecting Behavior Science Claritymentioning
confidence: 99%
“…Food security is a priority for all countries around the world. In the Western world, food security of often taken for granted (Fieldhouse and Thompson, 2012;Charlebois and Vandertuin, 2021). Becoming more food autonomous is known to be a continuing pursuit for most countries around the world (Benke and Tomkins, 2017;Kolinjivadi, Mendez and Dupras, 2019).…”
Section: Food Autonomy and Consumer Perceptionmentioning
confidence: 99%
“…However, most of these preliminary studies were made at an early stage of the pandemic when the situation was still developing, leading to controversial results in the amount of waste generated compared with a pre-pandemic scenario. For example, Charlebois et al [14] and Zand and Heir [15] found an increase in food waste in Canada and Tehran, respectively, and Principato et al [16] and Fan et al [17] found the opposite in Italy and Shanghai, respectively. These pioneering studies, with some exceptions [3,18], gathered data during the lockdown for short periods (a few months) and were focused on the household fraction [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%